The Value of Computation: A Few Illustrative Examples. Issue 5 (28th May 2023) - Diamond, Harvey
ABSTRACT: This paper presents a series of basic computational problems that are mathematically and/or graphically appealing, and provides an idea of places one might go in trying to understand what is happening, integrating mathematics, computation, and graphics. The real point of this paper is to make a case, through those examples, for computation as an early and integral part in the undergraduate mathematics curriculum. By computation we mean the ability to rapidly and easily program exploratory calculations, and as well display the results with a versatile suite of graphics capabilities. The problems used here, and the philosophy behind them, derive from a MATLAB -based course in computation, programming, and mathematical applications that the author has taught for over 10 years.